PENGUATAN KEPEMIMPINAN MANAJERIAL PERGURUAN TINGGI ISLAM MELALUI PENDAMPINGAN TATA KELOLA DAN PEMETAAN RANTING ILMU DOSEN - Mawardi; Mona Novita; Husni Hidayat; Firdaus; Muhammad Adly; Emilda Amini (LPPM STAI Muhammadiyah Probolinggo, 2026)
Strengthening managerial leadership is a strategic aspect in improving the quality of governance in Islamic higher education institutions, particularly in facing the challenges of increasingly complex and data-driven higher education transformation. However, academic management is often not supported by an integrated lecturer competency mapping system, hampering institutional strategic planning. This community service activity aims to develop a model for strengthening managerial leadership through mentoring lecturers' governance and branch mapping at UNISBA using a Community-Based Participatory Research (CBPR) approach. Implementation methods included collaborative Focus Group Discussions (FGDs), co-design of branch mapping, and joint policy validation involving structural officials, internal institutions, and lecturers as active partners. The results of the activity demonstrated increased participatory leadership capacity, the development of a data-based branch mapping model, and the strengthening of a more transparent, collaborative, and adaptive governance system tailored to the needs of the institution. The integration of Islamic leadership values ​​such as trustworthiness and deliberation also strengthens an organizational culture oriented toward accountability and sustainability. This mentoring model has the potential to become a good practice in developing participatory managerial leadership-based governance in Islamic higher education institutions.